2022
DOI: 10.1007/s11625-022-01119-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of a nature-based program in fostering multiple connections to nature

Abstract: Reconnecting to nature is imperative for the sustainability of humans on Earth, offering a leverage point for system change. Connections to nature have been conceptualized as a typology of five types as follows: material; experiential; cognitive; emotional; and, philosophical, ranging from relatively shallow to deeper connections, respectively. Educational programs that immerse individuals in nature have been designed to build an appreciation for places travelled, awareness of environmental issues and to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…A relationship between egocentricism and connection to nature via its material consumption is consistent with a good deal of thinking in environmental behaviour research [46,54,55] and sustainable consumption [47]. Baird, Dale, Holzer, Hutson, Ives and Plummer [14] for example refer to materialism as representing a "shallow connections to nature" (p. 3) recognising its basis in anthropocentrism and distinguishing it from "deeper" forms of connection such as cognitive and emotional connections.…”
Section: Value Orientations and Cn Class Membershipsupporting
confidence: 57%
See 3 more Smart Citations
“…A relationship between egocentricism and connection to nature via its material consumption is consistent with a good deal of thinking in environmental behaviour research [46,54,55] and sustainable consumption [47]. Baird, Dale, Holzer, Hutson, Ives and Plummer [14] for example refer to materialism as representing a "shallow connections to nature" (p. 3) recognising its basis in anthropocentrism and distinguishing it from "deeper" forms of connection such as cognitive and emotional connections.…”
Section: Value Orientations and Cn Class Membershipsupporting
confidence: 57%
“…The AIMES is based on Ives, et al [13] theoretical model of CN that highlights multiple ways of connecting to nature: material, experiential, cognitive, emotional, and philosophical. Recent work by Baird, et al [14] successfully demonstrated the use of this framework by showing how outdoor based nature programs influence the five connection types identified by Ives, Abson, von Wehrden, Dorninger, Klaniecki and Fischer [13]. Furthermore, Riechers, et al [15] found this multi-dimensional conceptualisation useful in describing the effects of landscape change on CN.…”
Section: The Multidimensional Aimes Connection To Nature Scalementioning
confidence: 97%
See 2 more Smart Citations
“…With further research, scholars have argued that cognitive and affective factors play an important driving role in tourists’ pro-environmental behavior ( Baird et al, 2022 ). Among the existing research, few studies have explored the influencing factors that affect tourists’ pro-environmental behavior through motivation-opportunity-ability (MOA) theory and cognitive-affective-conative (CAC) theory conjointly.…”
Section: Introductionmentioning
confidence: 99%